Estimated COVID-19 vaccine effectiveness against seroconversion from SARS-CoV-2 Infection, March–October, 2021. Issue 15 (6th April 2023) - Plumb, Ian D.; Fette, Lida M.; Tjaden, Ashley H.; Feldstein, Leora; Saydah, Sharon; Ahmed, Amina; Link-Gelles, Ruth; Wierzba, Thomas F.; Berry, Andrea A.; Friedman-Klabanoff, DeAnna; Larsen, Moira P.; Runyon, Michael S.; et al.
Highlights: COVID-19 vaccine effectiveness might be estimated using SARS-CoV-2 serology. A nested case control analysis estimated effectiveness during March–October 2021. Vaccine effectiveness against seroconversion was 88% after 2 mRNA doses. Estimated effectiveness was similar to estimates produced using virologic methods. Abstract: Background: Monitoring the effectiveness of COVID-19 vaccines against SARS-CoV-2 infections remains important to inform public health responses. Estimation of vaccine effectiveness (VE) against serological evidence of SARS-CoV-2 infection might provide an alternative measure of the benefit of vaccination against infection. Methods: We estimated mRNA COVID-19 vaccine effectiveness (VE) against development of SARS-CoV-2 anti-nucleocapsid antibodies in March–October 2021, during which the Delta variant became predominant. Participants were enrolled from four participating healthcare systems in the United States, and completed electronic surveys that included vaccination history. Dried blood spot specimens collected on a monthly basis were analyzed for anti-spike antibodies, and, if positive, anti-nucleocapsid antibodies. We used detection of new anti-nucleocapsid antibodies to indicate SARS-CoV-2 infection, and estimated VE by comparing 154 case-participants with new detection of anti-nucleocapsid antibodies to 1, 540 seronegative control-participants matched by calendar period. Using conditional logistic regression, we estimated VE ≥ 14 days after the 2nd dose of an mRNA vaccine compared with no receipt of a COVID-19 vaccine dose, adjusting for age group, healthcare worker occupation, urban/suburban/rural residence, healthcare system region, and reported contact with a person testing positive for SARS-CoV-2. Results: Among individuals who completed a primary series, estimated VE against seroconversion from SARS-CoV-2 infection was 88.8% (95% confidence interval [CI], 79.6%–93.9%) after any mRNA vaccine, 87.8% (95% CI, 75.9%–93.8%) after BioNTech vaccine and 91.7% (95% CI, 75.7%–97.2%) after Moderna vaccine. VE was estimated to be lower ≥ 3 months after dose 2 compared with < 3 months after dose 2, and among participants who were older or had underlying health conditions, although confidence intervals overlapped between subgroups. Conclusions: VE estimates generated using infection-induced antibodies were consistent with published estimates from clinical trials and observational studies that used virologic tests to confirm infection during the same period. Our findings support recommendations for eligible adults to remain up to date with COVID-19 vaccination.